AN ADOLESCENT WITH UNEXPLAINED DIABETES MELLITUS AND ASSOCIATED CONGENITAL GENITOURINARY ANOMALIES: A CASE REPORT - Ong , Jayne AX; Hussain, Suhaimi (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Maturity-onset diabetes of the young (MODY) is a rare form of diabetes found in Malaysia and worldwide, with at least 14 recognized types linked to different genetic mutations. MODY Type 5 (MODY 5) is caused by mutations in the HNF1 gene, which encodes hepatocyte nuclear factor 1 beta. This condition is characterised by diabetes and various extra-pancreatic features, including abnormalities in the kidneys and urogenital system. CASE We present a young female patient who initially presented with diabetes mellitus, later diagnosed with congenital renal anomalies, including a right single kidney and Müllerian anomalies. Her strong family history of diabetes and renal issues underscores the importance of recognising this diagnosis. A diagnosis of a monogenic form of diabetes was suspected since she had an onset of diabetes at the age of 13 years, absent acanthosis nigricans, positive family history with onset less than 30 years old and renal/Müllerian duct abnormalities. A targeted gene panel, whole exome sequencing panel, was performed to test for MODY. The panel indicated a positive result for the HNF1B gene mutation c.766C>T (p. Pro256Ser), resulting in an amino acid change at codon 256 from proline to serine (p. Pro256Ser). CONCLUSION This case highlights the importance of recognising the potential overlap between diabetes, renal disorders and Müllerian anomalies, particularly in young patients without a clear family history. Genetic testing is the gold standard for diagnosing MODY, but access and affordability can be challenging for patients in Malaysia.